Teacher professional learning and development for a future-oriented education system – a “wicked problem”? - Gilbert, J (Australian Association for Research in Education (AARE), 2014)
In this presentation we present some initial findings from a research project designed to explore the kinds—and level—of support a group of teachers needed to experience the “step change” in thinking that (we argue) they need to become “future-oriented” educators. Background One strand of the educational futures literature argues that today’s schools are no longer “fit for purpose”. The context they were set up to serve has changed, but, as Richard Slaughter put it (25 years ago), schooling continues to “unthinkingly reproduce an obsolete world-view”. However, while there is now a great deal of talk about the needs of “21st century” learners, there is very little discussion of what 21st century teachers might look like, or how today’s teachers might become more “future-oriented”. This project was set up to explore this territory. The project Its starting point was that becoming a “future-oriented” teacher involves something more than accepting and implementing constructs developed by others: it involves major cognitive shift. The project’s aim was to investigate whether or not this kind of cognitive shift is possible for teachers enculturated in 20th century thinking, and, if it is, what helps it to occur? Drawing on the adult cognitive development and “transformational learning” literatures, we developed an “intervention”, which was made up of a university paper, a workshop on adult development, and cluster workshops. We then developed a research project that was designed to evaluate the effects of this intervention. Participants in the research project were interviewed three times, observed in the workshops, and asked to write monthly reflections on their thinking during and after the intervention. This paper reports on a snapshot of the findings from this project (which is ongoing) and our reflections on what these findings mean for the future of this kind of work. Our experience in this project has made us want to think beyond the individual-oriented methodologies we used in this work. Our ongoing work in this area is informed by complex adaptive systems theory. We are now treating the intervention as a “safe-to-fail” experiment, in the sense in which this term is used by Snowden et al. We are interested in discussing these ideas with other researchers using them in educational contexts. 1. Slaughter, R. (2988). Futures. In D. Hicks (Ed.). Education for peace: Issues, principles and practice in the classroom. (pp. 214-228). London: Routledge. 2. E.g. Kegan, R. (1994). In over our heads: The mental demands of modern life. Cambridge MA: Harvard University Press; Mezirow, J. & associates (eds.) Learning as transformation: Critical perspectives on a theory in progress. San Francisco: Jossey-Bass. 3. E.g. Snowden, D. (2002). Complex acts of knowing: Paradox and descriptive self-awareness. Journal of Knowledge management 6(2), pp.100-111; Snowden, D. (2007). Safe-fail probes. http://cognitive-edge.com/blog/entry/4090/safe-fail-probes;Kurtz, C. & Snowden, D. (2003). The new dynamics of strategy: Sense-making in a complex and complicated world. IBM Systems Journal, 42(3), 462.